2010
DOI: 10.1148/radiol.09082074
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and Urinary Tract Imaging: Triple-Bolus Multidetector CT Urography as a One-Stop Shop—Protocol Design, Opacification, and Image Quality Analysis

Abstract: Triple-bolus multidetector CT urography is a dose-efficient protocol acquiring corticomedullary-nephrographic-excretory and vascular enhancement phases in a single acquisition and provides sufficient opacification and distention of the UUT. Simultaneously, adequate image quality of renal parenchyma and vascular anatomy is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 37 publications
1
53
0
2
Order By: Relevance
“…The 28.7% reduction in CTDIvol and 40.7% reduction in DLP followed a similar trend to previously reported data 8 . Clinical implications of these findings are significant.…”
Section: Summary Of Study Resultssupporting
confidence: 91%
“…The 28.7% reduction in CTDIvol and 40.7% reduction in DLP followed a similar trend to previously reported data 8 . Clinical implications of these findings are significant.…”
Section: Summary Of Study Resultssupporting
confidence: 91%
“…The use of CTU in haematuria is increasing as the availability of CT scanners improves and the radiation dose is minimised using techniques such as double or triple bolus contrast administration [4,5]. The impact of incidental findings is therefore increasing, and this study has identified the cost implication associated with this.…”
Section: Discussionmentioning
confidence: 93%
“…CTU has become more widely accessible, with an increased number of CT scanners globally. Additionally, the high radiation dose associated with CTU has been significantly reduced with the newer double and triple bolus techniques [4,5]. When CTU is performed as the primary imaging modality in haematuria, it reduces the number of patients who undergo CTU following an inadequate IVU.…”
mentioning
confidence: 99%
“…split-bolus technique) [38,39] • Adjustment of image quality reference values of the automatic tube current modulation for oversized patients [40] • Reduction of the tube voltage and/or tube current for survey CT [41,42] • Positioning of the X-ray tube below the table for the survey CT (e.g. 180°, postero-anterior position) [41,42] • Prevention of the routine use of narrow collimations (e.g.…”
Section: Resultsmentioning
confidence: 99%